Epidemiology of bovine herpes virus-1 under different housing practices in cattle breeding stations - CHANDRANAIK, B M; RATHNAMMA, D; PATIL, S S; RANGANATHA, S; KOVI, RAMESH C; AKHILA, D S; ISLOOR, SHRIKRISHNA; RENUKAPRASAD, C; PRABHUDAS, K (The Indian Journal of Animal Sciences, 2014)
Present paper describes the dynamics of bovine herpes virus-1(BoHV-1) in breeding cattle under different housing, feeding and watering practices. Organized breeding farms A, B, C, D were selected for this study. In farm A, the animals were housed in large open shed with common grazing and drinking area. Farm B had individual pens with separate feeding facility but with common watering/drinking facility. Farm C had had individual pens, with separate feeding and drinking facility for each animal. Farm D possessed modern individual housing system with separate feeding, drinking facility, restricted personnel entry and better bio-security set up. The blood and semen samples / vaginal swabs were collected from 177 animals. Avidin- biotin ELISA recorded BoHV-1 antibodies in 56, 38.77, 21.05 and 17.5% animals in farm A, B, C and D respectively. A TaqMan probe real time PCR targeting the BoHV-1 gB gene was standardised and this assay detected BoHV-1 in 11, 3 and 3 animals in Farm A, B and C respectively. None of the samples collected from Farm D were positive for BoHV-1 by real time PCR. The study recorded higher seroprevalence as well as virus transmission in farms that had housing systems allowing closer animal to animal contacts. In view of the different modes adopted by BoHV-1 in transmission through susceptible populations, the study recommends better bio-secured housing systems that avoid closer animal to animal contacts, for production of BoHV-1 free semen and calves at breeding stations.